2010
DOI: 10.1243/09544054jem1662
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of laser machining of carbon-fibre-reinforced composites

Abstract: The growing use of carbon-fibre-reinforced polymer (CFRP) composites as high-performance lightweight materials in aerospace and automotive industries demands efficient and low-cost machining technologies. The use of laser machining for cutting and drilling composites is attractive owing to its high speed, flexibility, and ease of automation. However, the anisotropic material properties of composites, and issues related to the heat-affected zone (HAZ), charring, and potential delamination during laser processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…Once the temperature reaches the vaporization temperature of the matrix, the matrix along the conduction path evaporates. This zone where the matrix loss occurs due to photothermal conduction is known as the heat-affected zone (HAZ) [52]. It has been shown that the size of the HAZ depends on the laser scanning speed, direction, power and frequency as these variables determine the energy absorbed into the material [52,30].…”
Section: Assessment Of Modifications In the Surface Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Once the temperature reaches the vaporization temperature of the matrix, the matrix along the conduction path evaporates. This zone where the matrix loss occurs due to photothermal conduction is known as the heat-affected zone (HAZ) [52]. It has been shown that the size of the HAZ depends on the laser scanning speed, direction, power and frequency as these variables determine the energy absorbed into the material [52,30].…”
Section: Assessment Of Modifications In the Surface Morphologymentioning
confidence: 99%
“…This zone where the matrix loss occurs due to photothermal conduction is known as the heat-affected zone (HAZ) [52]. It has been shown that the size of the HAZ depends on the laser scanning speed, direction, power and frequency as these variables determine the energy absorbed into the material [52,30]. Figure 8 also shows optical images taken from three selected regions that are representative of the three groups mentioned above.…”
Section: Assessment Of Modifications In the Surface Morphologymentioning
confidence: 99%
“…The influence of different process parameters including laser wavelengths, beam transverse mode, pulse duration, repetition rate, laser power density, fluence (energy density), beam spot size, scanning speed and machining strategy were investigated [5,[9][10][11][12][13][14][15][16][17][18][19][20][21]. Li et al [9] investigated the machining quality of CFRP using a diode-pumped solidstate UV laser.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is considered as a critical quality parameter in assessing the quality of the laser cutting of CFRP composites in this work. The large difference in thermal properties between the two constituent materials of CFRP composites results in excessive heat-affected zones [10]. This is considered as the major obstacle for wide industry applications of laser machining of CFRP composites.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that minimum HAZ (around 30-50 lm) can be obtained using a nanosecond pulsed UV laser. Negarestani et al [10] developed a three-dimensional model to simulate the transient temperature field and subsequent material removal on a heterogeneous fibre-matrix mesh in laser machining of CFRP composite. They predicted the dimensions of the HAZ during laser machining of CFRP.…”
Section: Introductionmentioning
confidence: 99%